The Effect of Material Conveyances on Workload, Musculoskeletal Disorders, Productivity and Performance in the Process of Plate Cutting - I Nyoman Sutarna; I Nengah Ludra Antara; Daud Simon Anakottapary (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
The use of material conveyances that are not in accordance with the concept of ergonomics harm the human body. Repair of work brushes by applying ergonomics to material conveyances can reduce the risk category. The purpose of this study was to determine the effect of material conveyance on reducing workload, musculoskeletal disorders, increasing productivity and performance. The study was conducted using the same subject design method with a sample of 16 workers. The data were analyzed by paired t-test with a significant level of p<0.05. The results of the analysis showed that the PO workload data was 104.4 beats per minute, P1 was 93.5 beats per minute there was a decrease of 10.9 beats per minute or 10.4%, PO musculoskeletal complaints were 80.1 scores, P1 was 70.0 the scores were decreased by 10.1 or 12.6%, PO productivity of 0.201, P1 of 0.355, an increase of 0.154 or 43.4%. The conclusion is that the use of material conveyances means a decrease in workload, musculoskeletal disorders, an increase in productivity and performance. It is recommended to workers to use material conveyances equipment in carrying out transport and material transport activities.